Implementation of online interactive read-aloud lessons with picture books to improve the reading learning experiences of fifth graders at a private school in Floridablanca, Santander (2021)
This research report presents the procedure and results of an action research study aimed at determining the ways in which the implementation of interactive read-alouds with pictures books in online sessions affected the reading learning experiences of a group of fifth-graders at a private school in Floridablanca, Santander. Twenty-nine fifth graders participated in the study for over seven months during 2019 and 2020. Data were collected through classroom observation, diagnostic tests, teacher’s journals, class videos, and a survey. These data were analyzed through process coding to determine the effects of implementing the proposed strategy. The outcomes of the strategy were quite positive. The findings revealed that the pedagogical intervention influenced the students’ reading learning experiences in two main ways: First, it enriched their learning experiences by improving the quality and quantity of interactions in L1 and L2, and by promoting more positive attitudes towards reading in English. Second, the pedagogical intervention led the teacher to monitor and adapt her teaching, and these changes improved the students’ overall learning experience. The study derived some implications for teachers willing to carry out similar pedagogical interventions.